Behavior-Based Safety Analysis with Unsafe Action and Unsafe Condition in Cadets at The General Workshop of Medan Aviation Polytechnic - Ivana Wardani; Fauziah Nur; Inda Tri Pasa; Liber Tommy Hutabarat; Sukarwoto Sukarwoto (Jurnal Indonesia Sosial Sains, 2024)
This study aims to analyze the implementation of Behavior Safety (BBS) and identify factors related to Unsafe Actions and Unsafe Conditions in cadets at the General Workshop of Medan Aviation Polytechnic. The research method used was survey and observation, involving the active participation of cadets as respondents. Data were collected through questionnaires and direct observation of behaviors and conditions that could pose risks in the work environment. The results of the analysis showed that the implementation of BBS had a positive impact in increasing cadets' awareness and compliance with safety procedures. However, the findings also identified a high number of Unsafe Actions, such as inappropriate use of personal protective equipment or negligence in following safety procedures. In addition, Unsafe Conditions were also detected in several areas, such as unsuitability of work equipment and lack of preventive maintenance. This research provides in-depth insight into the factors causing Unsafe Actions and Unsafe Conditions so that concrete corrective measures can be taken to improve safety at the General Workshop of Medan Aviation Polytechnic. The implication of this research is expected to contribute to the development of a more effective security policy and improved work safety for cadets in carrying out activities in the workshop environment.